(untitled) (Bangladesh Journal of Zoology, 2020)
Forty-two freshly defecated fecal samples from captive Asiatic Black Bear (Ursus thibetanus) were collected between May 2017 and April 2018 from Bangladesh National Zoo, Dhaka, Shaheed A.H.M. Central Park and Zoo, Rajshahi and Bangabandhu Sheikh Mujib Safari Park, Gazipur. The collected samples were processed by Formol-ether concentration technique. Altogether nine different gastrointestinal (GI) parasites were observed and identified, which include one protozoan, Coccidia spp. (42.86%); four cestodes, Hymenolepis spp. (42.86%), Diphyllobothrium spp. (28.57%), Spirometra spp. (14.29%) and Taenia spp. (21.43%); and four nematodes Ascaris spp. (57.14%), Toxocara spp. (21.43%), Trichuris spp. (21.43%) and hookworms (35.71%). No trematode parasite was found during the study period. Dominance of helminth parasites (71.43%) over protozoan parasites was observed. The male bears were found more susceptible to parasitic infection than the females. The intensity of infection was found erratic in young and adult bears. The species diversity, animals feeding behavior and hygiene maintenance may be responsible for the high prevalence rate of gastrointestinal parasites in the present study. Bangladesh J. Zool. 48(1): 119-125, 2020